SNAGS EXPIRATION FOR COMMUNITY DEVELOPMENT WITH TELUGU FOLK MEDIA (International Journal of Food and Nutritional Sciences, 2019)
"Folk" refers to practices that have been handed down from generation to generation and haveendured for an extended period of time in a particular group. It can be transmitted either orallyor by written text. Folk culture refers to the culture of early humans who were nomadic andshared an oral history.